2020
DOI: 10.1002/anie.202004950
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Dimeric Manganese‐Catalyzed Selective Hydroarylation of Internal Alkynes

Abstract: We have developed a general and site‐predictable manganese‐catalyzed hydroarylation of internal alkynes in the presence of water, under an air atmosphere without the involvement of ligand. The unique catalytic feature of this reaction is highlighted by comparison with other widely used transition metal catalysts including palladium, rhodium, nickel, or copper. The simple operation, high efficiency and excellent functional group compatibility make this protocol practical for more than 90 structurally diverse in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…The Xie group has recently expanded on this reactivity and devised a ligand-free manganese-catalyzed hydroarylation of tert-propargylic alcohols with boronic acids (Scheme 5b). 21 The reaction conditions are very user-friendly, tolerating the presence of water and an air atmosphere. Although the scope is limited to tertiary alcohols, the regioselectivity was complete, and the functional group compatibility was exceptionally high.…”
Section: Hydroarylation Of Internal Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Xie group has recently expanded on this reactivity and devised a ligand-free manganese-catalyzed hydroarylation of tert-propargylic alcohols with boronic acids (Scheme 5b). 21 The reaction conditions are very user-friendly, tolerating the presence of water and an air atmosphere. Although the scope is limited to tertiary alcohols, the regioselectivity was complete, and the functional group compatibility was exceptionally high.…”
Section: Hydroarylation Of Internal Alkynesmentioning
confidence: 99%
“…The Xie group has recently expanded on this reactivity and devised a ligand-free manganese-catalyzed hydroarylation of tert -propargylic alcohols with boronic acids (Scheme b) . The reaction conditions are very user-friendly, tolerating the presence of water and an air atmosphere.…”
Section: Hydroarylation Of Internal Alkynesmentioning
confidence: 99%
“…Despite the wealth of reactivity that has been established in the catalytic functionalization of alkynes toward the construction of stereochemically defined olefins, 9 11 unsymmetrical dialkyl-substituted alkynes are noticeably absent from most contributions and, when present, typically provide unsatisfactory levels of reactivity and/or regioselectivity. 12 In an effort to enhance the involvement of this class of alkynes, our group has reported an indirect solution that relies on the use of a propargylic SO 2 Py directing group for achieving site-selectivity control. 13 In our previously reported Pd-catalyzed hydroarylation reaction, it was found that monodentate phosphine ligands significantly outperformed their bidentate analogues because they allow the alkyne substrate to accommodate through bidentate coordination in the ligand sphere of the metal, facilitating the regioselective insertion of the Pd–Ar σ-bond.…”
Section: Introductionmentioning
confidence: 99%
“…[4] In this context, the manganesecatalyzed chelation-assisted alkenylation of (hetero) arene CÀ H bonds with alkynes has become the subject of increasing research attention in synthetic community. [4][5][6] In 2013, the Wang group first described the alkenylation of (hetero)arene CÀ H bonds with terminal alkynes using Mn(CO) 5 Br as the catalyst. [5a] Thereafter, terminal alkynes have been intensively explored in Mn-catalyzed (hetero)arene CÀ H bond alkenylation by the groups of Lei and Li, [5b] Wang, [5c,g] Ackermann, [5d] and others, [5e,f,h-j] and Mn(CO) 5 Br catalyst in combination with a base or acid additive or both worked well for these transformations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, less success has been achieved with the more challenging internal alkynes, and only a handful of procedures are available. [6] 2-Pyridones are key structural units in numerous biologically active natural products and pharmaceuticals, [7] and also acts as valuable building blocks for the construction of important Nheterocycles. [8] As such, ever-growing research atten-tion has been focused on the development of efficient protocols for the synthesis of functionalized 2pyridones.…”
Section: Introductionmentioning
confidence: 99%